2001
DOI: 10.1007/s11743-001-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

31P nuclear magnetic resonance studies on alkyl phosphate emulsifiers in cosmetic oil‐in‐water emulsions

Abstract: Cosmetic oil-in-water emulsions with a stearyl phosphate emulsifier are examined by means of static and dynamic 31 P nuclear magnetic resonance (NMR) techniques to characterize the molecular properties of the emulsifier in situ. The interfacially bound emulsifier can be detected by highresolution NMR spectroscopy, whereas the excess emulsifier exists as a solid lipid phase not detectable by this technique. The emulsions and the emulsifier raw material, consisting of monostearyl phosphate as well as distearyl p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Some emollients can also have an inherent UV absorption that increases the broad spectrum of protection. Emulsifiers are amphiphilic molecules that reduce interfacial tension between two immiscible liquids playing an important role in the stability of the emulsion, consistency, skin feel and care properties of the formulation (Al-Bawab and Friberg, 2006;Plass et al, 2001). The emulsifier system defines the emulsion type: traditionally, oil-in-water (O/W) or waterin-oil (W/O) system (Osterwalder et al, 2014).…”
Section: Main Components Of Sunscreensmentioning
confidence: 99%
“…Some emollients can also have an inherent UV absorption that increases the broad spectrum of protection. Emulsifiers are amphiphilic molecules that reduce interfacial tension between two immiscible liquids playing an important role in the stability of the emulsion, consistency, skin feel and care properties of the formulation (Al-Bawab and Friberg, 2006;Plass et al, 2001). The emulsifier system defines the emulsion type: traditionally, oil-in-water (O/W) or waterin-oil (W/O) system (Osterwalder et al, 2014).…”
Section: Main Components Of Sunscreensmentioning
confidence: 99%
“…We report here the first 31 P and 35 Cl diffusion studies on transition-metal complexes (using their phosphine ligands and perchlorate anions) and suggest that these nuclei provide a useful addition to either 1 H or 19 F PGSE probes. 31 P PGSE diffusion studies have been previously used to study phosphorus-containing metabolites in vivo, emulsions, and the mass transport of phosphoric acid in water …”
Section: Introductionmentioning
confidence: 99%
“…Studies in our laboratory revealed that structural information on commercially available cosmetic formulations having many ingredients can also be obtained by means of NMR spectroscopy. It is essential that this method can measure sample volumes in the cubic centimeter range without influencing the system studied and especially any chemical equilibria that may be present.…”
mentioning
confidence: 99%